Environmental toxicology - Mommsen, T. P. (Thomas P.); Moon, T. W. (Thomas W.) (Amsterdam ; Boston : Elsevier, 2005)
This sixth volume in this established series deals with the biochemical responses of fish to different environmental/ecological factors. Environmental Toxicology captures vital issues affecting the responses of fish to the chemical surroundings of their environment. Chapters included in this volume identify the systems found in fish to deal with xenobiotics, hormonal interactions initiated in the presence of these chemicals, the unique mechanisms used by fish to adjust to the present chemicals, and the new and evolving mixtures of chemicals in their environment. Also included, is a crucial review of the new methods being applied in fish systems to understand the effects of xenobiotics to fish fitness - a key theme in environmental health and critical to the future of fish populations. * Entirely new topic discussion and most recent volume in the acclaimed series * Includes chapters detailed on a cellular level * Introduces discussion of pharmaceutical effects on fish.
The utility of zebrafish as a model for toxicological research / Michael J. Carvan III, Tisha King Heiden and Henry Tomasiewicz -- Use of fish cell lines in the toxicology and ecotoxicology of fish : piscine cell lines in environmental toxicology / N.C. Bols, V.R. Dayeh, L.E.J. Lee and K. Schirmer -- Approaches in proteomics and genomics for eco-toxicology -- Nancy D. Denslow, Iris Knoebl and Patrick Larkin -- Interactions between lipids and persistent organic pollutants in fish / Adria A. Elskus, Tracy K. Collier and Emily Monosson -- Metabolic fate of nonylphenols and related phenolic compounds in fish / Jean-Pierre Cravedi and Daniel Zalko -- Pesticide biotransformation in fish / Daniel Schlenk -- Xenobiotic receptors in fish : Structural and functional diversity and evolutionary insights / Mark E. Hahn, Rebeka R. Merson and Sibel I. Karchner -- Impacts of environmental toxicants and natural variables on the immune system of fishes / Karen G. Burnett -- Fish models of carcinogenesis / Gary K. Ostrander and Jeanette M. Rotchell -- Metallothionein : structure and regulation / Peter Kling and Per-Erik Olsson -- Cell death : investigation and application in fish toxicology / Antony W. Wood, David M. Janz and Glen J. Van Der Kraak -- Adrenal toxicology : environmental pollutants and the HPI axis / Alice Hontela -- Xenobiotic impact on corticosteroid signaling / Mathilakath M. Vijayan, Patrick Prunet and Adrienne N. Boone -- Thyroid hormones / J.G. Eales and S.B. Brown -- The biology and toxicology of retinoids in fish / D. Alsop, Glen J. Van Der Kraak, S.B. Brown and J.G. Eales -- Vitellogenesis and endocrine disruption / Naoshi Hiramatsu, Ann O. Cheek, Craig V. Sullivan, Takahiro Matsubara and Akihiko Hara -- Pharmaceuticals in the environment : drugged fish? / Vance L. Trudeau, Chris D. Metcalfe, Caroline Mimeault and Thomas W. Moon -- P-glycoproteins and xenobiotic efflux transport in fish / Armin Sturm and Helmut Segner.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Environmental toxicology; Fishes -- Effect of chemicals on; Hazardous Substances -- Αdverse effects; Hazardous Substances -- Τοxicity; Environmental Pollution -- Αdverse effects; Electronic books